Peran Pemerintah Desa dalam Meningkatkan Partisipasi Masyarakat dalam Pembangunan Desa - Mondong, Hendra (GOVERNANCE, 2013)
Village Government in carrying out their duties and responsibilities has obstacles and problems. Obstacles and problems include: lack of human resource of vilaggeâ€™s staffs, lack of facilities and infrastructure work, as well as the income is also low. Government in the implementation of development policies, not fully open and the transparent government as it also have not fully cooperated with the entire community and in motivating the public to preserve the existing development. Therefore, as the village head of the village government to always do the activities and always pay attention to things like reasons the author described above, which is primarily in terms of execution and implementation of development policies, because according to the community where they feel that is what will they hold such as the head of the village in organizing the construction and implementation of the policy must be optimal and open to the public in providing participation should be higher. Regarding the ability of village government in the implementation of policy and the government's ability to mobilize the participation of the village community, then it can be understood how extensive and complex problems faced by the village government in the implementation of policies to increase community participation in development and community organizing. In the implementation of the government's job as an administrator in the field of social development and can be categorized already succeeded, because the village government and government officials often go directly to the field by monitoring or Â to control any development activities that directly executed. Keywords: participation, human resources, development